2022
DOI: 10.3389/fvets.2022.812710
|View full text |Cite
|
Sign up to set email alerts
|

Producer Perceptions Toward Prevention and Control of Lameness in Dairy Cows in Alberta Canada: A Thematic Analysis

Abstract: Lameness in dairy cattle poses both an animal welfare and economic threat to dairy farms. Although the Canadian dairy industry has identified lameness as the most important health issue, lameness prevalence in the province of Alberta has not decreased over the last decade. Factors related to lameness have been reported, but the prevalence remains high. Therefore, this study was conducted to investigate dairy producers' perceptions on lameness and how these perceptions influence lameness prevalence in their cow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…However, in the Albertan study, investigating hoof trimming strategies [ 13 ], it is not mentioned whether farmers trimmed lame cows themselves in between hoof trimming visits by a hoof trimmer. Moreover, in another Albertan study, dairy farmers reported that lameness is hard to diagnose and often only severely lame cows are recognized and might therefore be addressed differently on farms [ 18 ]. One New Zealand study addresses the issue of the interval between detection of and treatment for lameness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in the Albertan study, investigating hoof trimming strategies [ 13 ], it is not mentioned whether farmers trimmed lame cows themselves in between hoof trimming visits by a hoof trimmer. Moreover, in another Albertan study, dairy farmers reported that lameness is hard to diagnose and often only severely lame cows are recognized and might therefore be addressed differently on farms [ 18 ]. One New Zealand study addresses the issue of the interval between detection of and treatment for lameness.…”
Section: Discussionmentioning
confidence: 99%
“…With estimated costs per case of SU of US$216, SU are reported to be the most expensive non-infectious hoof lesion, with the most recent estimation of milk loss being the main contributor to the costs of SU [ 20 ]. However, we also know that not all cows diagnosed with SU have concurrent gait abnormalities or producers are unsuccessful in identifying lame cows [ 3 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation